Development Of Sidangke Mobile Learning To Improve Stunting Literacy In Enrekang Regency - Rahmat; Abdullah Pandang; Mustafa (International Journal of Education Management and Religion, 2026)
This study reports the development and evaluation of SIDANGKE (Sistem Informasi Stunting Kabupaten Enrekang), a mobile learning application designed to improve public literacy on stunting prevention in Enrekang Regency, South Sulawesi, Indonesia. The research adopted an applied Research and Development (R&D) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The application was developed based on community needs, local health data, and instructional design principles to ensure contextual relevance and usability. Data were collected through interviews, observations, expert validation instruments, and pre-test and post-test assessments involving parents of toddlers, community health cadres, and health practitioners. The data were analysed using descriptive statistics and inferential analysis, including expert validation scores and the N-Gain test to measure effectiveness. The results indicate that the SIDANGKE application achieved a content and media validity score of 91.8%, classified as very high, and a practicality score of 89.6%, indicating strong usability and user acceptance. Furthermore, the effectiveness analysis produced an N-Gain value of 0.67, reflecting a moderate-to-high improvement in users’ knowledge and understanding of stunting causes, prevention strategies, and early intervention practices. These findings demonstrate that mobile learning can serve as an effective medium for community-based health education, particularly in rural areas with limited access to conventional learning resources. The study supports mobile learning theory, multimedia learning principles, and health literacy frameworks, while also aligning with regional stunting reduction policies and national digital transformation initiatives. Overall, SIDANGKE represents a valid, practical, and effective digital innovation that can be scaled and replicated to strengthen community health literacy and support sustainable stunting prevention programmes in Indonesia.